Development and validation of a novel multiplexed DNA analysis system, InnoTyper® 21. (July 2017) - Brown, Hiromi; Thompson, Robyn; Murphy, Gina; Peters, Dixie; La Rue, Bobby; King, Jonathan; Montgomery, Anne H.; Carroll, Marion; Baus, James; Sinha, Sid; Wendt, Frank R.; Song, Bing; et al.
Highlights: Developmental validation of a novel, Alu-based DNA typing system, InnoTyper 21. InnoTyper 21 yields fragment sizes 63–124 bp making it suitable for degraded samples. Highly sensitive; valuable results with as low as 25 pg input DNA. Total power of discrimination for 20 loci > 1 in 3.8 million for populations tested. Greater statistical power over haplotype systems typically used in degraded samples. Abstract: We report here a novel multiplexed DNA analysis system consisting of 20 Alu markers and Amelogenin for analysis of highly degraded forensic biological samples. The key to the success of the system in obtaining results from degraded samples is the primer design yielding small amplicon size (60–125 bp) for all 20 markers. The markers included in the InnoTyper ® 21 system are bi-allelic, having two possible allelic states (insertion or null) and thus termed INNULs. The markers are short interspersed nuclear elements (SINEs), a category of retrotransposable elements (REs) which are non-coding genomic DNA repeat sequences, or "mobile insertion elements, " comprising approximately 40% of the human genome. Alu elements are primate specific SINEs that have reached a copy number in excess of one million in the human genome, which makes these markers highly sensitive and desirable for forensic samples with extremely degraded DNA. Until now however, due to the inherent size difference associated with insertion and no insertion alleles, the use of Alu REs has not been practical for forensic applications. The novel primer design described herein has allowed the development of a multiplexed Alu system yielding fragment sizes amenable to degraded DNA samples, as frequently encountered in missing persons cases or forensic samples such as hair shafts. Although use of Alu s in human identity has been studied using single marker amplification and reported before, we report for the first time development and validation of a system with multiplexed RE markers. Studies performed include PCR optimization, species specificity, sensitivity, degradation and inhibition, precision and accuracy, nonprobative samples, mixture, and population database studies. A population study using 592 samples including five populations was performed using InnoTyper 21. The data indicated the random match probability for the combination of these 20 Alu markers was greater than 1 in 3.8 million for the populations studied, indicating the greater statistical power of these autosomal nuclear DNA markers over haplotype systems typically used in such degraded samples. Results demonstrate the system is successful in obtaining results from highly degraded DNA. A sensitivity study performed demonstrated at least 95% recovery of alleles from as low as 50 pg of total input DNA, and partial profiles from as low as 25 pg. This study has demonstrated that the bi-allelic INNULs in the InnoTyper 21 system provide a sensitivity of detection and a power of discrimination that makes them useful for human identification of extremely degraded samples.